Aplikasi Aktuator Pneumatik sebagai Simulator Beban Dinamis Vertikal pada Mekanisme Suspensi Roda Kendaraan Seperempat - Ka’ka, Simon; Himran, Syukri; Renreng, Ilyas; Sutresman, Onny (Politeknik Negeri Ujung Pandang, 2018)
Driving comfort for riders and passengers is a keytarget to be achieved. Fluctuations in vehicle loads, bumps,perforated surfaces, and other road damage will greatly affectthe vehicle suspension working system. This study aims tocalculate the vertical dynamic load of the vehicle actually whichoccurs on road construction after through the vehicle wheelsuspension mechanism. The Pneumatic cylinder that was drivenby pressurized air directly weigh on the spring and ShockAbsorber that contained on the wheels of the vehicle. The loadfluctuations of the medium weight category vehicle aredetermined by the regulation of the amount of pressurized airentering into the pneumatic cylinder chamber pushing the pistonand connecting rods. The deviation that occurs duringcompression on the Spring and Shock Absorber, is substitutedinto the vehicle dynamic load equation by taking also themagnitude of the spring stiffness constant, and the fluid or gascoefficient of the damper. The results showed that the magnitudeof the displacement when the compression force worked hassignificantly influenced the amount of vertical dynamic load ofthe vehicle that overlies the road construction. Experimentalresults using pneumatic actuators instead of real dynamic vehicleloads illustrate the characteristics of the relationship betweenwork pressure and dynamic load. If the working pressure of P2(bar) is given great, the vertical dynamic load Ft (N) whichoverloads the structure of the road is also greater. From thegraph shows that shock absorbers have greater ability to reducedynamic load vertically when compared to spring ability.